Public works engineering in local government - Clarke, R. H. (Thomas Telford, 1996)
This guide to the planning and implementation of public works describes the system, how to work within it and achieve the best results. This book defines local government infrastructure and policies, the concept of service, the character of public sector organisations, the roles of politicians and professionals and the nature of local democracy.